Foundations, schools and the state: school improvement partnerships in Germany and the United States as legitimacy-generating arrangements - Thümler, Ekkehard (Public management review, 2011)
The public school systems of both Germany and the United States face environmental pressures to provide better and more equitable results, while at the same time they are criticized for high degrees of bureaucracy and structural inertia. Public-private partnerships are frequently praised for their potential to provide a remedy to these deficits. In this article, I investigate the role of private philanthropic foundations that co-operate with public actors in school improvement partnerships. Drawing on institutional theory and empirical data derived from the exploratory research project ‘Strategies for Impact in Education’, the article concludes that an important function of such arrangements is the generation of legitimacy in case of ‘successful failure’.